Degradation of Methyl Green Dyes with ZnO Catalyst using the Photosonolysis Method - Muhammad Gani Ariski; Hary Sanjaya; Alizar Alizar; Deski Beri; Yohandri Yohandri (Departemen Kimia FMIPA UNP, 2022)
Textile and dyestuff industrial dye waste remain the most difficult wastewater to treat due to the complex aromatic molecular structure of industrial dyes, which are very difficult to decompose. This research was conducted on the degradation of methyl green using the photosonolysis method. The purpose of this study was to determine the optimum time and amount of ZnO used in degrading methyl green dye. The results of the percentage degradation were obtained from the absorbance value measured using a UV-Vis Spectrophotometer. (λmax) Methyl green obtained from the measurement of a UV-Vis spectrophotometer was 640 nm. The results showed that the optimum irradiation and sonication time to degrade methyl green was 60 minutes with a degradation percentage of 92.77%. For the effect of mass variation of ZnO catalyst obtained the optimum mass of 0.05 grams with a degradation percentage of 96.38%.